GREGORIO OSSA CERDA AND “OSSA Y ESCOBAR” . A MINING DEVELOPMENT BANK, C. 1855 - 1884. - Valenzuela, Luis (Revista de Historia Social y de las Mentalidades, 2025)
In this article, the author analyzes an example of credit institutions who have been founded at 1850s to foment the mining activity in Atacama†Ÿs zone. The firm “Ossa y Escobar”, was created in 1855 by the rich Copiapó banker Grego rio Ossa Cerda, and became one of the most important mining ventures of a zone in rapid growth due to the discovery of rich silver mines in Tres Puntas and Chimbero, in the 1840s, and subsequently, extended to the Bolivian mine camp of Caracoles, discovere d in 1870. However, the firm did not diversify its activities, and this, plus the decadence of mining in Atacama, carried the firm to its final liquidation in 1884.